Beyond Engagement: Integrating AR and VR for Inclusive Learning in K–Higher Education - Maulidah, Ghoniyatul; Christyodetaputri, Jihaan Haniifah (Yayasan Sinergi Kawula Muda, 2025)
This narrative review examines the integration of Augmented Reality (AR) and Virtual Reality (VR) technologies in education, with a focus on their impact, challenges, and implications for future research and policy. The study aims to evaluate how immersive learning environments contribute to improved engagement, conceptual understanding, skill development, and inclusivity across various educational levels. A systematic search of scholarly databases including Scopus, Web of Science, Google Scholar, and ERIC was conducted using a combination of targeted keywords. Inclusion criteria encompassed peer-reviewed studies published between 2015 and 2024 that analyzed AR/VR applications in formal education. The findings indicate that AR and VR significantly enhance motivation, academic performance, and practical competencies in students, especially within STEM, healthcare, and engineering disciplines. Comparative evidence shows notable advantages for learners using immersive tools versus traditional instruction. Furthermore, AR/VR applications support inclusive education by addressing the needs of students with learning difficulties. However, the review identifies persistent systemic barriers, including inadequate infrastructure, limited teacher training, and lack of strategic policy support, which impede broader adoption. This review underscores the urgent need for comprehensive policies, infrastructure investment, and sustained teacher development to harness the full potential of AR and VR in education. It calls for further interdisciplinary research to explore long-term outcomes, user experiences, and equitable access, thereby guiding effective integration of immersive technologies into future-ready educational systems.